ANALISIS INDEKS DAYA SAING DAERAH KABUPATEN WONOGIRI DAN KEBIJAKAN PENGEMBANGAN PADA SISTEM PERWILAYAHAN SUBOSUKAWONOSRATEN - Suranny, Lilyk Eka (Inisiasi, 2025)
The Regional Competitiveness Index is a description of the level of productivity, development, and independence of a region. The Regional Competitiveness Index (IDSD) is measured based on 4 components/aspects, 12 pillars, 23 dimensions and 48 indicators for districts/cities. This study aims to (1) Analyze the results of the IDSD of Wonogiri Regency, (2) Analyze the Needs and Development Strategy of the Subosukawonosraten Regional System based on the IDSD results, (3) Prepare recommendations for cooperation and collaboration agendas in the Subosukawonosraten Regional System. The score of the Regional Competitiveness Index (IDSD) measurement results for Wonogiri Regency in 2023 is 3.39. The IDSD score of Wonogiri Regency is lower when compared to the IDSD score of Central Java, which is 3.89 and also slightly below the national IDSD score, which is 3.44. The recommended development strategies for the Subosukawonosraten regional system, based on the IDSD results, include: Strengthening infrastructure to facilitate and facilitate accessibility to the agricultural, industrial, and tourism sectors; Improving regional fiscal policy by optimizing the tax sector and increasing the productivity of financial services and regionally-owned enterprises (BUMD); Strengthening collaboration and cooperation with pentahelix elements in developing regional innovation; and Strengthening the branding of Wonogiri Regency. Collaboration and sharing of Subosukawonosraten regional programs are planned to boost regional competitiveness, optimize superior agricultural commodities as the largest contributor to regional GDP, and provide public services to the community.